Prenatal diagnosis and postnatal management of congenital unilateral hydrocephalus for stenosis of the foramen of Monro - Pietro Spennato, MD; Gabriele Saccone, MD; Andrea Fratta, MD; Maria Rosaria Scala, MD; Laura Sarno, MD; Elisabetta Gragnano, RN; Fulvio Zullo; Giuseppe Cinalli, MD (Radiology Case Reports, 2021)
Congenital hydrocephalus and ventriculomegaly can be diagnosed reliably with prenatal ultrasound and Magnetic Resonance Imaging (MRI). Unilateral hydrocephalus is uncommon, and the prognosis depends on etiology and postnatal management. Here, we present a case of a 32-years-old woman with prenatal diagnosis of unilateral hydrocephalus associated with stenosis of the foramen of Monro. Unilateral hydrocephalus is an uncommon feature that can be detected prenatally on ultrasound and MRI. In case of isolated stenosis of the foramen of Monro prognosis is good.